Tanzania HIV Investment Case (IC) 2.0: Using modeling to explore optimization under severe resource constraints. (2021) - Hiebert, Lindsey; Resch, Stephen; Schutte, Carl; Turay, Mohamed; Zekeng, Leopold; Matiku, Sode; Semini, Iris; Stover, John; Forsythe, Steven; Hecht, Robert
No abstract available